Pitchfork Regulates Primary Cilia Dizsassembly and Left-Right Asymmetry - Kinzel, Doris (2010)
A variety of developmental disorders have been associated with ciliary defects, yet the controls that govern cilia disassembly are largely unknown. Here we report a mouse embryonic node gene, which we named Pitchfork (Pifo). Pifo associates with ciliary targeting complexes and accumulates at the basal body during cilia disassembly. Haploinsufficiency causes a unique node cilia duplication phenotype, left-right asymmetry defects, and heart failure. This phenotype is likely relevant in humans, because we identified a heterozygous R80K PIFO mutation in a fetus with situs inversus and cystic liver and kidneys, and in patient with double-outflow right ventricle. We show that PIFO, but not R80K PIFO, is sufficient to activate Aurora A, a protooncogenic kinase that induces cilia retraction, and that Pifo/PIFO mutation causes cilia retraction, basal body liberation, and overreplication defects. Thus, the observation of a disassembly phenotype in vivo provides an entry point to understand and categorize ciliary disease.